Fifty years of geophysical researches of glaciers in Institute of Geography, the Russian Academy of Sciences, 1966–2016 - V. Kotlyakov M.; Yu. Macheret Ya.; В. Котляков М.; Ю. Мачерет Я. (Ice and Snow, 2016)
In 1967‑2015, Institute of Geography of the USSR/Russian Academy of Sciences together with other organizations carried out field expeditions in different areas of mountain and polar glaciations in many regions: the Polar Urals, Caucasus, Pamir, Zailiysky and Jungar Alatau, Tien‑Shan, Pamir‑Alai, the Kamchatka Peninsula, the Pyrenees, the Arctic – Spitsbergen, Novaya Zemlya, Franz Josef and Severnaya Zemlya, and Antarctica – on the ice flow B, and in the sub‑Antarctic – Islands King George, Galindez, and Livingston. The gravimetric and ground and aerial radar observations were made in these expeditions. About 300 glaciers of different morphological types and sizes with cold, subpolar and temperate thermal regime were studied. Basic results of these studies are the following: (1) the new data on the ice thicknesses, ice volumes, subglacial relief, internal structure, and thermal state of the glaciers were obtained; (2) the two‑layered (polythermal) glaciers consisting of the upper layer of cold ice and the lower layer of temperate water‑filled ice had been revealed in Svalbard for the first time; spatial distribution of cold, polythermal and temperate glaciers had been determined; (3) the evidences were obtained that measured changes in thickness of the upper cold ice layer in polythermal glaciers can be used to estimate the long‑period variations of regional climates and serve as regional paleothermometers; (4) methods for estimating the water content in temperate and polythermal glaciers from the RES data were developed; and its space‑time variations in temperate ices of the Svaldbald glaciers were estimated since even small water content inside of them can noticeably change their dynamic behavior; (5) methods for estimating the ice volume within glaciers in large regions of mountain and polar glaciations had been created; the ice storages were estimated in Svalbard, Franz Josef Land, Dzhungrsky Alatau, the Great Caucasus, and Mt. Elbrus; (6) detailed data on the ice thicknesses and the subglacial relief had ...